2013
DOI: 10.1021/ja312030e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of SnO2 Nanocrystals and Surface-Bound Water Species

Abstract: The structure of SnO2 nanoparticles (avg. 5 nm) with a few layers of water on the surface has been elucidated by atomic pair distribution function (PDF) methods using in situ neutron total scattering data and molecular dynamics (MD) simulations. Analysis of PDF, neutron prompt gamma, and thermogravimetric data, coupled with MD-generated surface D2O/OD configurations demonstrates that the minimum concentration of OD groups required to prevent rapid growth of nanoparticles during thermal dehydration corresponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 57 publications
7
65
0
Order By: Relevance
“…The level of agreement reached at the end of the process (χ 2 = 0.30, 0.48 in terms of R w as defined in PDFgui 45 ) is relatively large compared with some high quality PDF refinements of disordered crystalline materials (R w ≈ 0.08 in perovskites 47 and R w ≈ 0.05 in chalcogenides. 48 However, the agreement is similar to what is achieved for other amorphous materials and nanoparticles, including gold nanoparticles (R w ≈ 0.26), 49 water molecules on SnO 2 nanoparticles (R w ≈ 0.19), 50 and our previous DFT-PDF iterative methodology investigation on metakaolin (R w ≈ 0.77). 24 To determine the exact medium range changes that occur during the crystalline-to-amorphous transition, the main contributing atom−atom correlations are displayed in Figure 4a and b for the nesquehonite (after the DFT energy minimization, structure B) and hydrated AMC (structure K), respectively.…”
Section: ■ Materials and Methodssupporting
confidence: 81%
“…The level of agreement reached at the end of the process (χ 2 = 0.30, 0.48 in terms of R w as defined in PDFgui 45 ) is relatively large compared with some high quality PDF refinements of disordered crystalline materials (R w ≈ 0.08 in perovskites 47 and R w ≈ 0.05 in chalcogenides. 48 However, the agreement is similar to what is achieved for other amorphous materials and nanoparticles, including gold nanoparticles (R w ≈ 0.26), 49 water molecules on SnO 2 nanoparticles (R w ≈ 0.19), 50 and our previous DFT-PDF iterative methodology investigation on metakaolin (R w ≈ 0.77). 24 To determine the exact medium range changes that occur during the crystalline-to-amorphous transition, the main contributing atom−atom correlations are displayed in Figure 4a and b for the nesquehonite (after the DFT energy minimization, structure B) and hydrated AMC (structure K), respectively.…”
Section: ■ Materials and Methodssupporting
confidence: 81%
“…25 Upon further hydration, a second (L 2 ) and third layer (L 3 ) will form whose structure depends on the degree of dissociation of L 1 . These layers are defined by distinct minima in the axial density profile of oxygen atoms perpendicular to the surface derived from our previous results, 36,37,43 and constitute 1 ML in L 1 , ∼1.7 ML in L 2 , and ∼1.3 ML in L 3 per Sn 2 O 4 (110) surface unit area. Figure 3 shows the INS spectra (measured at 7 K to minimize Debye−Waller effects on the measured spectra) for SnO 2 nanoparticulate samples at two hydration levels, full hydration (full: L 1 + L 2 + L 3 + a little extra water, or 4.4 ML) and driest achievable experimental state before the onset of nanoparticle destabilization and growth (dry: L 1 + 0.25L 2 , or 1.5 ML).…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…In the presence of even low water vapor pressures a complete L 1 layer develops where the oxygen atom of the water forms a covalent bond with the undercoordinated Sn v and creates a terminal water (TW). 36,37,43 If one of the protons of TW transfers to the adjacent BO site, terminal and bridging hydroxyls (TH and BH) will form. These L 1 configurations are shown in Figures 1 and 2 43 demonstrated that (i) the L 1 water can only be removed at high temperature (>250°C) under vacuum, (ii) L 2 stabilizes the nanoparticles studied here and in ref 43, and (iii) the presence of L 1 species subtly influences the nanoparticle crystalline structure (further evidence of strong water−surface interactions).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations